2012
DOI: 10.1074/jbc.m111.314088
|View full text |Cite|
|
Sign up to set email alerts
|

Metastasis-associated Protein 1 Drives Tumor Cell Migration and Invasion through Transcriptional Repression of RING Finger Protein 144A

Abstract: Background:The mechanistic role of MTA1 in tumor aggressiveness is yet to be deciphered. Results: RNF144A is a direct target of transcriptional repression by MTA1 and inhibits migration and invasion. Conclusion: Transcriptional repression of RNF144A by MTA1 confers a migratory and invasive phenotype of cancer cells. Significance: This study provides novel mechanistic insights into regulation of tumor progression by MTA1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…It will be very interesting to determine whether VCP is also involved in RNF144A-DNA-PKcs regulation in the future. A previous study suggested that RNF144A suppresses tumor migration and invasion (8). Our study identifies a previously unidentified role for RNF144A in apoptosis induction through suppression of the prosurvival signaling function of DNA-PKcs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It will be very interesting to determine whether VCP is also involved in RNF144A-DNA-PKcs regulation in the future. A previous study suggested that RNF144A suppresses tumor migration and invasion (8). Our study identifies a previously unidentified role for RNF144A in apoptosis induction through suppression of the prosurvival signaling function of DNA-PKcs.…”
Section: Discussionsupporting
confidence: 54%
“…RNF144A is able to interact with E2-conjugating enzymes UbcH7 and UbcH8 through its RING1 domain, and mutations on IBR or RING2 reduce this E2-E3 interaction (7). In addition, RNF144A is transcriptionally repressed by metastasis-associated protein 1 and inhibits migration and invasion in breast tumor cells (8). However, whether RNF144A is involved in apoptosis and DNA damage response (DDR) remains unexplored.…”
mentioning
confidence: 99%
“…Recent reports also identified MTA1-NuRD as a new HIC1 corepressor that targets the HiREs (HIC1 binding sites) in the promoters of Cyclin D1 [90], p57KIP2 [90], and EphA2 [91] in WI38 cells. In addition, MTA1 was also observed to be involved in the transcriptional repression of Six3 [29,92], p21 WAF1 [37], MMP-9 [93], RNF114A [94], SMAD7 [95], and PTEN [93] via NuRD.…”
Section: Mta1 As a Co-repressor Of Gene Transcription Through The Nurmentioning
confidence: 97%
“…Earlier studies have demonstrated that MTA1 forms a corepressor complex with HDAC1/2 and is recruited to the target gene promoters, thereby repressing gene transcription (29). For example, the MTA1⅐HDAC2 complex was identified as a transcriptional corepressor of number of tumor suppressor genes such as BRAC1, p21WAF1, and RNF144, where the MTA1⅐HDAC2 complex recruits onto their promoters and down-regulates the expression of these genes, leading to accelerated tumor growth and metastasis (32,41,42). In this study, we identified MTA1 as a transcriptional corepressor of the tumor suppressor gene PTEN, but contrary to earlier studies, for the first time, we found that MTA1 but not MTA2 associates with class II HDAC4s and identified the first target of the MTA1⅐HDAC4 containing the NuRD complex, the PTEN.…”
Section: Mta1 Expression Inversely Correlates With Pten Expresmentioning
confidence: 99%